The rooster and the cats - Rao; Vijaya (Kuala Lumpur Mind to Mind publication, 2006)
story that follows the adventures of a rooster who finds himself in a tricky situation with a group of cunning cats. As the The rooster tries to outwit the cats and avoid becoming their meal, he uses his cleverness and resourcefulness to navigate various challenges. The story highlights themes of ingenuity and bravery, showing how quick thinking and bravery can help one overcome seemingly impossible odds. The narrative is engaging and designed to entertain young readers while imparting a valuable lesson about using one's wits to solve problems.